Desenvolvimento econômico do estado do Tocantins: uma análise utilizando os métodos constant-market-share e estrutural-diferencial para avaliar o comércio internacional e a composição da estrutura produtiva regional - Cruz, Francisco Viana (Universidade do Vale do Rio dos Sinos, 2023)
This study intends to analyze the state of Tocantins's production structure, focusing on various production sectors, especially the agricultural sector, and its connection to international commerce. For a deeper understanding of this structure and its impact on regional development, the Constant Market Share (CMS) model was employed, which is a technique utilized in international commerce analysis to break the variations in a country or region's exportations into different explanatory factors. Our research was focused on three of the most relevant Tocantins's exports: the temporary crops sector, with an emphasis on the production of soybeans and corn; the slaughtering and manufacturing of meat products, especially beef and the vegetable and animal oils and fats manufacturing sector. To analyze the job market's dynamics and productive composition in specific sectors compared to neighboring regions of the state of Tocantins from 2010 to 2020 using the structural-differential method, the results collected revealed a growth in job creation in the state of Tocantins. It's important to stress that the public sector has a specific influence on the state's employment structure. Another important observation is the industrial sector's near absence in the economy, which is reflected in the scarce distribution of jobs in these segments. This interconnection between production structure, international commerce and job and income creation is crucial for the economic development of any region.
Keywords: Desenvolvimento econômico; Estrutura produtiva; Constant-market-share; Mercado de trabalho; Método estrutural-diferencial; Economic development; Production structure; Constant market share; Job market; Structural differential method; ACCNPQ::Ciências Sociais Aplicadas::Economia